Development and evaluation of emulsion-based adjuvants for vaccines against Streptococcus suis and classical swine fever virus in swine - Thapa, Rashmi (My University, 2025)
Streptococcus suis and Classical Swine Fever pose significant threats to swine health worldwide, causing substantial economic losses in the pork industry. Effective vaccination is one of the most reliable strategies to control and prevent these infections. Adjuvants enhance immune responses, improve vaccine efficacy, and enable dose sparing, making them essential for large-scale immunization. Among various adjuvant types, emulsion-based systems are especially attractive due to their ability to promote strong humoral and cellular immune responses, extend antigen availability at the injection site, and support safe and scalable formulations. This thesis focuses on developing and evaluating physically stable emulsion adjuvants suitable for swine vaccines. Multiple adjuvants based on different synthetic paraffin oils in conjunction with a surfactant were used to produce the emulsion at the nanoscale. Key physiological properties like droplet size, polydispersity, zeta potential, and emulsion stability were systematically analyzed. The surfactant ratio was optimized to produce nanoscale droplets and ensure stable emulsion for veterinary use. OW-14 (previously established adjuvant) and OW-415 (experimental adjuvant); When co-administered with a subunit protein antigen and inactivated bacteria induced high levels of immune responses in pigs. Cytokine profiling at Days 7 and 28 post-vaccination revealed balanced systemic immune activation, with OW-415 showing modest elevations in IFN-[alpha] and IL-10, indicating potential immunomodulatory effects. These findings support the promise of OW-415 as safe, immunogenic, and physically stable adjuvants for swine vaccine development.
Keywords: Vaccine; Adjuvant; Streptococcus suis; Classical swine fever